Rota Viral Infection: A Significant Disease Burden to Libya. - Salem Alkoshi; Kacey Ernst; Namaitijiang Maimaiti; Maznah Dahlui (Tehran University of Medical Sciences, 2014)
Rotavirus is a common infection causing 450,000 deaths annually primarily in children 5 years and below. Despite the high burden of disease, little is known about the epidemiology of rotavirus in Libya. The aim of this study was to estimate the rotavirus disease burden among Libyan children.A cross-sectional study was carried out prospectively among children 5 years old and below between August 2012 and April 2013. Stool samples of children with diarrhea attending the outpatient department or admitted to the pediatric wards, at three public hospitals within the northwestern region of Libya were tested for rotavirus. The seasonality, symptomology demographics and outcomes of rotavirus cases were determined and compared to other diarrhea illnesses. An estimated incidence rate per 100,000 children aged 5 years and below was determined.A total of 545 children with diarrhea were identified for participation. Results of rotavirus immunoassays determined 57% of cases were caused by rotavirus. Inpatients were more likely to be rotavirus positive than outpatients (58% vs. 53%, P